Wesbite e-Commerce Lia Cake (Studi Kasus : Lia Cake di Desa Rumbai Jaya Kecamatan Kempas) - Dwi Yuli Prasetyo (JUTI UNISI, 2019)
A cottage industry business units on a small scale in a particular industry. These efforts usually uses only one or two of the House as the center of production, administration and marketing at once simultaneously. When viewed from venture capital and the amount of energy absorbed is certainly less than big companies in General. Proven internet technologies is one of the media information that is efficient and effective in the dissemination of information that can be accessed by anyone, anytime and anywhere. So it is with Lia Cake home industry, an industry of households should be able to make information services and promotions to attract the attention of consumers. In addition to accurate information, fast, and easy, information submitted should be packed with interesting. System sales cottage industry of Lia Cake was by way of phone or sms and is not yet online, to promote it only from the mouth to the mouth. Sales system in this way takes a long time in the sales process, then the system is judged less effective and efficient. If you only rely on sales system in a way that the income of this household industry entrepreneurs have not experienced a significant increase. In addition to this household industry feels judged a bit slow. Therefore be designed a system of online sales by using a website with the goal to minimize the time the sales process with the aim of can increase the sales volume of household industry revenues so it can increased and customers may affect booking products without having to come directly to the cottage industry of Lia Cake.